A high-hardness and high-elasticity memory nano-nylon resin and preparation method thereof

By introducing structural nano reinforcers, nano silica and other materials into nylon resin, combined with epoxy plasticizers and isophorone diisocyanate, a high-hardness and high-elastic memory nanonylon resin is prepared, which solves the shortcomings of nylon resin materials in hardness, elasticity and shape memory, and achieves high-performance and environmentally friendly material applications.

CN118530581BActive Publication Date: 2025-03-28SHENZHEN COARTS OPTICAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410730495.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-03-28
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

The existing nylon resin materials have shortcomings in hardness, elasticity and shape memory functions, which are difficult to meet the application scenarios of high performance requirements, and are also facing an increasing demand for environmentally friendly materials.

Method used

The formulation of high hardness and high elastic memory nanonylon resin, including nylon 12, structural nanoenhancers, nanosilica, maleic anhydride grafted polypropylene, epoxy plasticizers and isophorone diisocyanate, were prepared by extrusion and granulation processes.

Benefits of technology

It significantly improves the hardness, elasticity and shape memory performance of the material, is suitable for a variety of application areas with high performance and durability requirements, and also has the advantages of environmentally friendly plasticizers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a high-hardness, high-elasticity, memory nano-nylon resin and a preparation method thereof. The high-hardness, high-elasticity, memory nano-nylon resin comprises the following raw materials: 90-95 parts by weight of nylon; 2-6 parts by weight of structural nano-enhancer; 1-2 parts by weight of nano-silicon dioxide; 1-2 parts by weight of maleic anhydride grafted polypropylene; 0.5-1.5 parts by weight of epoxy plasticizer; 0.1-0.5 parts by weight of isophorone diisocyanate. The nano-nylon resin of the present invention combines nylon 12 with nano-filler structural nano-enhancer and silica, significantly improving the hardness and wear resistance, while optimizing the filler dispersion and material elasticity by adding maleic anhydride grafted polypropylene and epoxy soybean oil. The application of isophorone diisocyanate enhances the shape memory effect, ensuring that the material can return to its original shape after deformation. These characteristics make the resin perform well in high-performance applications, such as eyeglass frames, and meet environmental protection requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite resin material, in particular to a high-hardness and high-elasticity memory nano nylon resin and a preparation method thereof. Background Art

[0002] In the field of high-performance polymers, the pursuit of higher material performance has become an ongoing challenge, especially in terms of hardness, elasticity, wear resistance and shape memory function. Nylon resin, as a type of high-performance polymer widely used in products such as eyeglass frames and electronic equipment components, has excellent mechanical properties and processing properties, but its performance still has room for improvement under specific high-performance requirements. The performance limitations of traditional nylon resins lie in their deficiencies in hardness, elasticity and wear resistance, which affect the usability of the material in a wider range of application scenarios. In addition, with the advancement of science and technology and the development of market demand, the demand for environmentally friendly materials is increasing, especially innovative applications in shape memory functions, which are of great significance to enhancing product added value and user experience.

[0003] The modification research of nylon resin has always been one of the hot topics in materials science research. By introducing new nanofillers, crosslinking agents and plasticizers, the comprehensive performance of nylon resin is continuously optimized and improved. Among them, the introduction of shape memory function has opened up new application prospects for nylon resin materials, making it not only limited to traditional strength and durability requirements, but also able to automatically restore to the preset shape when subjected to certain external stimuli (such as temperature changes), showing the characteristics of smart materials. The realization of this intelligent shape memory function depends on the precise design and regulation of the internal microstructure of the material, which needs to be achieved through the cross-integration of nanotechnology and polymer chemistry.

[0004] At present, although there have been studies on modifying nylon resin by adding different nanofillers and chemical crosslinkers in order to improve its hardness, elasticity and shape memory effect, these modified materials often face the problem of poor effect. Therefore, developing a high-hardness and high-elastic memory nano nylon resin material with good shape memory performance has become a major challenge. Summary of the invention

[0005] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a high-hardness and high-elasticity memory nano-nylon resin and a preparation method thereof.

[0006] Specifically, the technical solution of the present invention is:

[0007] The invention provides a high-hardness and high-elasticity memory nano nylon resin, the raw materials of which include nylon, a structural nano reinforcing agent, nano silicon dioxide, maleic anhydride grafted polypropylene, an epoxy plasticizer and isophorone diisocyanate.

[0008] Preferably, a high-hardness and high-elastic memory nano-nylon resin comprises the following raw materials:

[0009] 90-95 parts by weight of nylon;

[0010] 2-6 parts by weight of structural nano-enhancer;

[0011] 1-2 parts by weight of nano silicon dioxide;

[0012] 1-2 parts by weight of maleic anhydride grafted polypropylene;

[0013] 0.5-1.5 parts by weight of epoxy plasticizer;

[0014] 0.1-0.5 parts by weight of isophorone diisocyanate.

[0015] Preferably, the nylon is nylon 66, nylon 6, nylon 11 or nylon 12.

[0016] Preferably, the nylon is nylon 12.

[0017] Preferably, the structural nano-reinforcement agent is at least one of cellulose nanocrystals, carbon nanotubes and carbon nanofibers.

[0018] Preferably, the structural nano-reinforcer is cellulose nanocrystals and / or carbon nanotubes. Preferably, the structural nano-reinforcer is cellulose nanocrystals and carbon nanotubes in a mass ratio of (1-3): (1-3).

[0019] Preferably, the carbon nanotubes have a diameter of 10-30 nanometers.

[0020] Preferably, the nano-silicon dioxide has a particle size of 10-50 nanometers.

[0021] Preferably, the epoxy plasticizer is at least one of epoxy soybean oil and di(2-ethylhexyl)-4,5-epoxytetrahydrophthalate.

[0022] The present invention also provides a method for preparing a high-hardness and high-elasticity memory nano-nylon resin, comprising the following steps: mixing nylon 12, a structural nano-enhancer, nano-silicon dioxide, maleic anhydride grafted polypropylene, an epoxy plasticizer, and isophorone diisocyanate; extruding; and granulating.

[0023] Preferably, a method for preparing a high-hardness and high-elasticity memory nano-nylon resin comprises the following steps:

[0024] (1) Dry nylon 12;

[0025] (2) mixing nylon 12, structural nano-reinforcement agent, nano-silica, maleic anhydride grafted polypropylene, epoxy plasticizer, and isophorone diisocyanate;

[0026] (3) Twin-screw extruder melt extrusion;

[0027] (4) Granulation.

[0028] Preferably, a method for preparing a high-hardness and high-elasticity memory nano-nylon resin comprises the following steps:

[0029] (1) Dry nylon 12 at 70-90°C for 12-24 hours in a hot air circulation oven;

[0030] (2) mixing nylon 12, structural nano-reinforcement agent, nano-silica, maleic anhydride grafted polypropylene, epoxy plasticizer, and isophorone diisocyanate in a high shear mixer at 1000-3000 rpm for 5-15 minutes;

[0031] (3) melt extrusion by a twin-screw extruder, wherein the inlet temperature is 178-185° C., the outlet temperature is 215-225° C., and the screw speed is 300-500 rpm;

[0032] (4) Water trough cooling and pelletizing by pelletizer.

[0033] The high-hardness and high-elasticity memory nano-nylon resin of the present invention adopts an optimized formula, combines the excellent mechanical properties and processability of nylon 12, and by adding an appropriate amount of structural nano-reinforcer and nano-silicon dioxide as reinforcing fillers, not only the hardness and wear resistance of the material are significantly improved, but also the conductivity is increased, so that it is suitable for various applications requiring conductivity. In addition, the introduction of maleic anhydride grafted polypropylene improves the interface compatibility between the filler and the nylon matrix, promotes the uniform dispersion of the nano-filler in the nylon matrix, thereby improving the overall mechanical properties and stability of the material. Epoxidized soybean oil, as an environmentally friendly plasticizer, enhances the flexibility and elasticity of the material, and further enhances the bending and torsion properties of the material when subjected to external forces. Isophorone diisocyanate, as a cross-linking agent, strengthens the shape memory ability of the material, enables the product to return to its original shape after the external force is removed, and provides an excellent "memory" effect for the material. Through this comprehensive formula design, the nano-nylon resin of the present invention shows excellent comprehensive performance and is suitable for use in a variety of application fields requiring high performance and durability, such as eyeglass frames, electronic equipment components, etc. DETAILED DESCRIPTION

[0034] A high-hardness and high-elasticity memory nano-nylon resin, comprising the following raw materials:

[0035] 90-95 parts by weight of nylon 12;

[0036] 2-6 parts by weight of structural nano-enhancer;

[0037] 1-2 parts by weight of nano silicon dioxide;

[0038] 1-2 parts by weight of maleic anhydride grafted polypropylene;

[0039] 0.5-1.5 parts by weight of epoxy plasticizer;

[0040] 0.1-0.5 parts by weight of isophorone diisocyanate.

[0041] The structural nano-enhancer is at least one of cellulose nanocrystals, carbon nanotubes and carbon nanofibers;

[0042] The carbon nanotube has a diameter of 10-30 nanometers;

[0043] The nano silicon dioxide particle size is 10-50 nanometers;

[0044] The epoxy plasticizer is at least one of epoxy soybean oil and 4,5-epoxytetrahydrophthalic acid di(2-ethylhexyl) ester.

[0045] As a high-quality polyamide resin, it contributes good mechanical properties, excellent processability, significant chemical resistance and low water absorption, ensuring that the composite material can perform well in a variety of demanding applications. The introduction of nylon 12 not only gives the composite material outstanding toughness and durability, ensuring the stability and reliability of the product when subjected to physical impact or chemical erosion, but also its low water absorption characteristics also ensure the dimensional stability of the finished product in a humid environment. In addition, the good processability of nylon 12 enables the present invention to more flexibly respond to the design and manufacturing requirements of complex shapes, greatly improving production efficiency and economy.

[0046] In the present invention, structural nano-reinforcers, including cellulose nanocrystals (CNCs), carbon nanotubes (CNTs) and carbon nanofibers (CNFs), are introduced to enhance the comprehensive properties of high-hardness and high-elasticity memory nano-nylon resin.

[0047] CNCs significantly improve the hardness and elasticity of composite materials with their excellent strength and modulus. Its unique multi-level structure is conducive to building a stable network in the nylon matrix, thereby improving the mechanical stability of the material. In addition, the addition of CNCs can optimize the shape memory behavior of the composite material. By promoting the orderly arrangement of nylon chains, it not only improves the fixation and recovery ability during the shape memory process, but also facilitates the storage and release of memory stress, improving the accuracy and speed of shape recovery.

[0048] CNTs effectively enhance the strength and toughness of composite materials by using their outstanding mechanical properties, electrical conductivity and thermal conductivity. The good dispersion and large specific surface area of ​​CNTs in the nylon matrix strengthen the interfacial bonding between the filler and the matrix, promote the effective conduction of stress in the composite material, and thus further improve the shape memory performance.

[0049] As a carbon-based nanomaterial with a special morphology, CNFs has a fibrous structure that forms an effective reinforcement network in the nylon matrix, improving the overall strength and toughness of the material. The introduction of CNFs also promotes the improvement of shape memory properties. Its unique fibrous structure and good interface compatibility improve the shape recovery and fixation effect of the composite material, especially when subjected to large deformation, it can still maintain excellent memory performance.

[0050] In summary, by combining the unique action mechanisms of these structural nanoreinforcements, not only the hardness, elasticity and wear resistance of nylon composites are significantly improved, but also their shape memory properties are finely optimized.

[0051] Nano-silica, as an inorganic nano-filler, can not only significantly improve the hardness and wear resistance of the material, but this feature is particularly critical for demanding application environments, such as eyeglass frames. It has good compatibility with the nylon matrix and strong interfacial interaction. Although nano-silica itself does not have shape memory function, it can indirectly promote the shape memory performance of the composite material. Specifically, it promotes the orderly arrangement of nylon chains at the microscopic level, thereby facilitating accurate fixation and efficient recovery of the shape during the shape memory process. In addition, nano-silica can also be used as an efficient dispersing aid to optimize the dispersibility of other structural nano-reinforcements such as CNCs and CNTs in composite materials, and further improve the comprehensive performance and durability of the material through uniform dispersion. Not only that, the introduction of nano-silica also optimizes the thermal properties of the composite material, improving both thermal stability and thermal conductivity.

[0052] Maleic anhydride grafted polypropylene (MA-g-PP) improves the compatibility between fillers and nylon matrix, and promotes the uniform dispersion of nanofillers such as structural nanoreinforcers and nanosilica in the polymer matrix. This improved compatibility and dispersibility not only helps to reduce the phase separation phenomenon inside the material, but also ensures the uniformity and stability of the composite material. The addition of MA-g-PP directly promotes the improvement of the overall mechanical properties and shape memory properties of the composite material by strengthening the interfacial bonding between the filler and the matrix. Good filler dispersion and enhanced interfacial interaction jointly optimize the microstructure of the composite material, thereby improving the speed and accuracy of shape recovery.

[0053] The unique epoxy groups of epoxidized soybean oil (ESO) can chemically crosslink or interact with the nylon matrix and nanofillers including structural nanoreinforcers and nanosilica. This process not only significantly enhances the overall mechanical properties and shape memory ability of the composite material, but also optimizes the toughness and flexibility of the composite material, thereby significantly improving the shape recovery speed and recovery accuracy of the material. In addition, the introduction of ESO also promotes the uniform dispersion of nanofillers in the nylon matrix, which further improves the hardness and wear resistance of the material.

[0054] As an epoxy plasticizer, 4,5-epoxytetrahydrophthalate (2-ethylhexyl) ester plays a key role in significantly improving the flexibility and elasticity of nano-nylon resins, while promoting a significant improvement in shape memory effects. This plasticizer chemically cross-links with the nylon matrix and other components such as structural nano-reinforcers and nano-silica through its epoxy groups to form a stable three-dimensional network structure. This process not only enhances the structural stability and mechanical strength of the material, but also improves the dispersion and compatibility of the filler in the matrix, thereby improving the overall performance of the material. More importantly, the chemical cross-linking of the epoxy groups helps to create physical anchor points inside the material, which can effectively help the material remember and return to its original shape after the material is deformed due to heat or force, thereby achieving good shape memory function.

[0055] As a cross-linking agent, isophorone diisocyanate supports the shape memory properties of the material by promoting the formation of a stable cross-linked network inside the composite material. This cross-linked network not only improves the structural stability of the material, but also creates physical anchor points that can effectively help the material remember and return to its original shape after it is deformed by heat or mechanical force. Through the action of isophorone diisocyanate, a strong network structure is formed inside the material, which can guide the material to return to its original state after the external force is eliminated, thereby achieving the effect of shape memory. Therefore, the application of isophorone diisocyanate not only significantly enhances the shape memory function of the material, but also improves the comprehensive performance and durability of the composite material, ensuring its high efficiency and long-term stability in a variety of applications.

[0056] In order to further optimize the performance or meet other specific application requirements, the present invention may further add other functional raw materials such as stabilizers, antioxidants, UV stabilizers, and colorants to achieve their corresponding functions.

[0057] Stabilizers and antioxidants are mainly used to prevent materials from degrading due to heat, oxidation and other factors during processing and use. They can capture free radicals, prevent chain breakage and cross-linking reactions, and thus improve the thermal stability and aging resistance of materials.

[0058] UV stabilizers can absorb UV light and convert it into heat that is harmless to the material, or scatter UV light to reduce the photodegradation of the material due to UV exposure, which can effectively extend the service life of the product and maintain its appearance and performance.

[0059] Colorants can provide a wide range of color options to meet different design and aesthetic requirements. By choosing the right colorant, you can give your product a specific color and appearance without affecting the performance of the material itself. In fashion products such as eyeglass frames, the right colorant can not only increase the market appeal of the product, but also be used for brand recognition and product differentiation.

[0060] The present invention also provides a method for preparing a high-hardness and high-elasticity memory nano-nylon resin, comprising the following steps:

[0061] (1) Nylon 12 drying: Use a hot air circulation oven to dry nylon 12 at 70-90°C for 12-24 hours. Although nylon 12 has a low water absorption rate, drying before processing can minimize the adverse effects of moisture on product performance, such as bubble formation or physical property degradation caused by high temperature.

[0062] (2) Pre-dispersion: Nylon 12, structural nano-reinforcement agent, nano-silica, maleic anhydride grafted polypropylene, epoxy plasticizer, and isophorone diisocyanate are mixed in a high shear mixer at 1000-3000 rpm for 5-15 minutes; the role of pre-dispersion is to improve the uniform dispersion of fillers in the nylon matrix. This can reduce filler aggregation and ensure its performance in the composite material, such as improving hardness and elasticity.

[0063] (3) Melt extrusion: melt extrusion is carried out through a twin-screw extruder, wherein the inlet temperature is 178-185°C, the outlet temperature is 215-225°C; the screw speed is 300-500rpm; all raw materials are melted and mixed to make the additives evenly distributed in the nylon matrix, and to promote chemical cross-linking reactions, and finally extruded.

[0064] (4) Granulation: water tank cooling, pelletizer granulation. The molten composite material is cooled and cut into pellets for subsequent processing. Water tank cooling is an effective method to quickly cool thermoplastic materials from a molten state to a solid state. A pelletizer is used to cut the cooled material into pellets of a specified size.

[0065] In the embodiments and comparative examples of the present invention, some raw materials are introduced as follows: cellulose nanocrystals, provided by Flash Technology Nanomaterials Co., Ltd., Zeta potential -50 eV, carbon nanotubes with a diameter of 20 nanometers, and nano-silicon dioxide particles with a diameter of 30 nanometers.

[0066] Embodiment 1:

[0067] A high-hardness and high-elasticity memory nano-nylon resin, comprising the following raw materials:

[0068] 92 parts by weight of nylon 12;

[0069] 4 parts by weight of structural nano-enhancement agent carbon nanotubes;

[0070] 1.5 parts by weight of nano silicon dioxide;

[0071] 1.5 parts by weight of maleic anhydride grafted polypropylene;

[0072] 1 part by weight of epoxy plasticizer epoxidized soybean oil;

[0073] 0.3 parts by weight of isophorone diisocyanate.

[0074] The preparation method thereof comprises the following steps:

[0075] (1) Dry nylon 12 at 80°C for 18 hours in a hot air circulation oven;

[0076] (2) mixing nylon 12, structural nano-reinforcement agent, nano-silica, maleic anhydride grafted polypropylene, epoxy plasticizer, and isophorone diisocyanate in a high shear mixer at 2000 rpm for 10 min;

[0077] (3) melt extrusion by a twin-screw extruder, wherein the inlet temperature is 180° C., the outlet temperature is 220° C., and the screw speed is 400 rpm;

[0078] (4) Water trough cooling and pelletizing by pelletizer.

[0079] Embodiment 2:

[0080] On the basis of Example 1, "4 parts by weight of structural nano-reinforcer carbon nanotubes" is replaced by "4 parts by weight of structural nano-reinforcer cellulose nanocrystals".

[0081] Embodiment 3:

[0082] On the basis of Example 1, "4 parts by weight of structural nano-reinforcer carbon nanotubes" is replaced by "2 parts by weight of structural nano-reinforcer cellulose nanocrystals and 2 parts by weight of structural nano-reinforcer carbon nanotubes".

[0083] Embodiment 4:

[0084] On the basis of Example 1, "1 part by weight of epoxy plasticizer epoxidized soybean oil" was replaced by "1 part by weight of epoxy plasticizer 4,5-epoxytetrahydrophthalic acid di(2-ethylhexyl) ester".

[0085] Embodiment 5:

[0086] On the basis of Example 1, "4 parts by weight of structural nano-reinforcer carbon nanotubes" is replaced by "2 parts by weight of structural nano-reinforcer cellulose nanocrystals and 2 parts by weight of structural nano-reinforcer carbon nanotubes"; "1 part by weight of epoxy plasticizer epoxidized soybean oil" is replaced by "1 part by weight of epoxy plasticizer 4,5-epoxytetrahydrophthalic acid di(2-ethylhexyl) ester".

[0087] Comparative Example 1:

[0088] Based on Example 1, the raw material structural nano-reinforcement agent is deleted.

[0089] Comparative Example 2:

[0090] On the basis of Example 1, the raw material nano silicon dioxide is deleted.

[0091] Comparative Example 3:

[0092] On the basis of Example 1, "1 part by weight of epoxy plasticizer epoxidized soybean oil" was replaced by "1 part by weight of phthalate plasticizer dilauryl phthalate".

[0093] Test example:

[0094] The material prepared in the example or comparative example was hot-pressed at a pressure of 10 MPa for 3 minutes and finally pressed into a strip of 150 mm×10 mm×3 mm.

[0095] Referring to the test method provided in the prior art, the shape memory effect is tested using an electronic universal testing machine with a temperature control chamber. The specific test method is as follows:

[0096] (1) Initial length determination: First, place the prepared specimen in an electronic universal testing machine with temperature control function. The initial length of the specimen is recorded as L0. Then, set the temperature to 190°C and maintain this temperature for 10 minutes to ensure that the specimen is fully thermally balanced.

[0097] (2) Deformation setting: After reaching temperature equilibrium, the spline is stretched to 200% of its original length at a fixed stretching rate of 10 mm / min, and this state is maintained for 10 minutes to complete the deformation setting. After the stretching is completed, the length of the spline at this time is recorded and recorded as L1.

[0098] (3) Shape fixation: Subsequently, the temperature of the testing machine was adjusted to 25°C and maintained for 10 minutes to allow the specimen to crystallize and fix at this temperature. After 10 minutes of stress removal, the length of the specimen was measured and recorded, and the length at this time was recorded as L2.

[0099] (4) Shape recovery: After that, the temperature was raised to 190°C again and maintained for 10 minutes, and then cooled to 25°C and maintained for 30 minutes to promote the recovery of the spline shape. Finally, the length of the spline at this time was measured and recorded, which was recorded as L3.

[0100] (5) Calculation of results:

[0101] Shape fixation rate R f =(L2-L0) / (L1-L0)×100%;

[0102] Shape recovery rate R r =(L2-L3) / (L2-L0)×100%.

[0103] Shape memory performance test table

[0104] <![CDATA[Shape fixing ratio R f , %]]> <![CDATA[Shape recovery rate R r , %]]> Example 1 94.0 91.7 Example 2 97.3 95.1 Example 3 98.2 96.5 Example 4 95.7 93.4 Example 5 99.4 98.3 Comparative Example 1 73.6 64.5 Comparative Example 2 90.9 87.1 Comparative Example 3 91.5 87.6

[0105] The high-hardness and high-elasticity memory nano-nylon resin of the present invention adopts a composite formula of structural nano-reinforcers such as cellulose nanocrystals, carbon nanotubes and carbon nanofibers, nano-silica, maleic anhydride grafted polypropylene and epoxy plasticizers such as epoxy soybean oil and 4,5-epoxytetrahydrophthalic acid di(2-ethylhexyl) ester, which significantly improves the shape memory performance of the nylon resin.

[0106] Comparing Examples 1-5 with Comparative Example 1, the structural nano-reinforcers play a key role in improving hardness and elasticity. Cellulose nanocrystals and carbon nanotubes can significantly enhance the mechanical properties of materials due to their high strength and modulus. These nano-reinforcers not only improve the hardness and elasticity of the composite material by forming a stable reinforcement network in the nylon matrix, but also promote the improvement of shape memory properties.

[0107] The composite use of cellulose nanocrystals and carbon nanotubes in Examples 3 and 5 demonstrated excellent shape fixation and shape recovery rates. CNCs optimize the mechanical balance of the composite material by providing high stiffness and crystallinity, while CNTs increase toughness and strength. This synergistic effect makes it easier and more accurate for the composite material to return to its original shape after being subjected to external forces, thereby improving the shape fixation and shape recovery speed. The differentiated surface properties between CNCs and CNTs further optimize the interfacial interaction between the filler and the matrix when acting together on the nylon matrix. This enhanced interfacial bonding not only improves the effective transfer of stress within the material, but is also crucial to improving shape memory performance. Through effective stress transfer, the uniform response of the composite material to external stimuli during the shape memory process is guaranteed, achieving a more consistent and rapid shape recovery effect.

[0108] Nano-silica indirectly affects the shape memory performance by improving the dispersibility of fillers in the nylon matrix. Although the absence of nano-silica in Comparative Example 2 leads to a decrease in the shape fixation rate and shape recovery rate, this effect is relatively small. This shows that nano-silica indirectly promotes the shape memory effect mainly by improving the hardness and wear resistance of the material.

[0109] Comparing Example 1, Example 4 and Comparative Example 3, epoxy plasticizers epoxidized soybean oil and 4,5-epoxytetrahydrophthalic acid di(2-ethylhexyl) ester show significant advantages in improving the shape memory ability of nano-nylon resin, mainly due to their unique chemical structure and mechanism of action. Epoxy plasticizers contain active epoxy groups, which can chemically crosslink with nylon molecular chains to form a stable three-dimensional network structure, significantly improving the structural stability and mechanical strength of the material, so that the material can be more effectively restored to its original state after being deformed. In addition, epoxy plasticizers can also improve the dispersibility and compatibility of nanofillers in the nylon matrix, enhance the intermolecular force, thereby improving the elastic modulus and shape recovery speed of the material. Higher thermal stability also ensures that the performance of the material does not degrade during the high temperature shape memory process. In contrast, phthalate plasticizers are relatively weak in promoting shape memory performance due to the lack of the ability to form effective chemical crosslinks.

[0110] Comparing Example 4 with Example 1, the epoxy plasticizer 4,5-epoxytetrahydrophthalic acid di(2-ethylhexyl) ester is significantly better than epoxy soybean oil in improving the shape memory performance of nano-nylon resin, mainly because of its higher epoxy group content and chemical reactivity, which enables it to form a more stable and dense three-dimensional cross-linked network with the functional groups in the nylon matrix. This network structure not only enhances the mechanical properties and thermal stability of the material, but also improves the compatibility and dispersibility with nanofillers, thereby achieving a better shape memory effect. In contrast, although epoxy soybean oil performs well as an environmentally friendly plasticizer in a variety of applications, its effect in promoting high-performance shape memory properties is limited by its low epoxy group reactivity and relatively weak chemical cross-linking ability. Therefore, 4,5-epoxytetrahydrophthalic acid di(2-ethylhexyl) ester shows a more obvious advantage in the design of nano-nylon resin materials that require highly precise shape recovery properties.

Claims

1. A high-hardness and high-elastic memory nano-nylon resin, characterized in that: Including the following raw materials: 90-95 parts by weight of nylon; 2-6 parts by weight of structural nano-enhancer; 1-2 parts by weight of nano silicon dioxide; 1-2 parts by weight of maleic anhydride grafted polypropylene; 0.5-1.5 parts by weight of epoxy plasticizer; 0.1-0.5 parts by weight of isophorone diisocyanate; The structural nano-reinforcement agent is composed of cellulose nanocrystals and carbon nanotubes in a mass ratio of (1-3): (1-3); The epoxy plasticizer is di(2-ethylhexyl)-4,5-epoxytetrahydrophthalate.

2. The high-hardness and high-elasticity memory nano-nylon resin according to claim 1, characterized in that: The nylon is nylon 66, nylon 6, nylon 11 or nylon 12.

3. The high-hardness and high-elasticity memory nano-nylon resin according to claim 1, characterized in that: The carbon nanotubes have a diameter of 10-30 nanometers.

4. The high-hardness and high-elasticity memory nano-nylon resin according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 10-50 nanometers.

5. The method for preparing the high-hardness and high-elasticity memory nano-nylon resin according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing nylon 12, structural nano-reinforcement agent, nano-silicon dioxide, maleic anhydride grafted polypropylene, epoxy plasticizer and isophorone diisocyanate; extruding; and granulating.

6. The method for preparing the high-hardness and high-elasticity memory nano-nylon resin according to claim 5, characterized in that: The steps include: (1) Dry nylon 12; (2) mixing nylon 12, structural nano-reinforcement agent, nano-silica, maleic anhydride grafted polypropylene, epoxy plasticizer, and isophorone diisocyanate; (3) Twin-screw extruder melt extrusion; (4) Granulation.

7. The method for preparing the high-hardness and high-elasticity memory nano-nylon resin according to claim 6, characterized in that: The steps include: (1) Use a hot air circulation oven to dry nylon 12 at 70-90°C for 12-24 hours; (2) mixing nylon 12, structural nano-reinforcement agent, nano-silica, maleic anhydride grafted polypropylene, epoxy plasticizer, and isophorone diisocyanate in a high shear mixer at 1000-3000 rpm for 5-15 minutes; (3) Melt extrusion through a twin-screw extruder, wherein the inlet temperature is 178-185°C, the outlet temperature is 215-225°C, and the screw speed is 300-500 rpm; (4) Water trough cooling and pelletizing by pelletizer.

Citation Information

Patent Citations

  • Carbon fiber / carbon nanotube enhanced nylon composite material, and preparation method thereof

    CN105400193A

  • High-conducting graphene modified nylon composite material and preparation method thereof

    CN107880538A

  • High-wear-resistance heat-conduction nylon composite material and preparation method thereof

    CN111909511A

  • Molecular orientation self-reinforced glass fiber reinforced plastic anchor rod and preparation method and application thereof

    CN117777672A